Awareness of Risk Factors among Persons at Risk for Lung Cancer, Chronic Obstructive Pulmonary Disease and Sleep Apnea: A Canadian Population-Based Study. Issue 6 (2010) - Walker, Shannon L; Saltman, David L; Colucci, Rosemary; Martin, Lesli
Abstract : OBJECTIVE: To assess awareness among persons at risk for lung cancer, chronic obstructive pulmonary disease (COPD) and sleep apnea regarding symptoms and risk factors of the disease, and their attitudes regarding the disease and toward those who are affected. METHODS: A quantitative hybrid telephone and Internet survey of a representative population of Canadian adults at risk for at least one of the three diseases was conducted. To measure the awareness and attitudes of First Nations, Inuit and Métis people to these diseases, a proportionate number were also surveyed. RESULTS: A total of 3626 individuals were contacted. Of these, 3036 (84%) were eligible to participate. Of those at risk for lung cancer and COPD, 65% and 69%, respectively, were due to tobacco smoke exposure. Among those at risk, 72% believed that they were informed about lung cancer compared with 36% for COPD and 56% for sleep apnea. Most respondents were knowledgeable about the common symptoms of lung cancer, COPD and sleep apnea, but were less aware of the impact lifestyle choices could have on the development of these disorders and the availability of treatment. Most of the participants (77%) believed that smoking was an addiction rather than a habit (19%). There were no significant differences in the awareness of risk factors, symptoms and attitudes toward all three lung diseases between First Nations, Inuit and Métis people and the general population. CONCLUSIONS: Canadians are reasonably aware of risk factors and symptoms for lung cancer and sleep apnea. However, there is poor awareness of COPD as a disease entity. There is a lack of appreciation for the impact lifestyle choices and changes can have on lung diseases.